2019
DOI: 10.29315/gm.v6i2.240
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da Alexitimia em Crianças Portuguesas com Perturbação de Hiperatividade/Défice de Atenção

Abstract: INTRODUÇÃO: Diversos estudos têm demonstrado existir uma perturbação do processamento emocional em crian-ças com perturbação hiperatividade/ défice de atenção (PHDA). No entanto, existem poucos estudos relativos à as-sociação entre alexitimia e PHDA tanto em adultos como em crianças, e nenhum na população portuguesa. MÉTODOS: A amostra acidental inclui 50 crianças previamente diagnosticadas com PHDA e sob tratamento e 51 crianças saudáveis sem PHDA, com idades compreendidas entre os 8 e os 17 anos. Com o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Sexual abuse is also cited as an explanatory variable of alexithymia, identified by Carneiro and Yoshida ( 2009 ). Several studies point to these variables as environmental variables, as predictors of problems in the circuit of emotions, specifically about recognizing feelings and respective responses (Teixeira et al, 2019 ). The indicial studies identified that most subjects with alexithymia had experienced traumatic events throughout their lives, which are predictors of alexithymia (Zeitlan & McNally, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual abuse is also cited as an explanatory variable of alexithymia, identified by Carneiro and Yoshida ( 2009 ). Several studies point to these variables as environmental variables, as predictors of problems in the circuit of emotions, specifically about recognizing feelings and respective responses (Teixeira et al, 2019 ). The indicial studies identified that most subjects with alexithymia had experienced traumatic events throughout their lives, which are predictors of alexithymia (Zeitlan & McNally, 1993 ).…”
Section: Discussionmentioning
confidence: 99%